Association between acetaminophen use and 30-day mortality in critically ill patients with pulmonary embolism: a retrospective cohort study using the MIMIC-IV database - Wang, Xincai; Lin, Xiankun; Qiu, Liman; Tu, Xunwei; Jiang, Linqian; Shang, Xiuling; Huang, Long (Frontiers in Pharmacology, 2025)
PurposePulmonary embolism (PE) has high mortality rates among critically ill patients. While acetaminophen shows potential therapeutic effects in critical illness, its impact on ICU patients with PE remains unclear. This study evaluated the association between acetaminophen use and 30-day mortality in ICU patients with PE.Patients and methodsA retrospective cohort study was conducted using the Medical Information Mart for Intensive Care IV (MIMIC-IV) database. Adult patients admitted to the ICU with confirmed PE between 2008 and 2022 were included. The primary exposure was acetaminophen use during the ICU stay, and the primary outcome was 30-day all-cause mortality. To control for confounding factors, propensity score matching (PSM) was applied, along with inverse probability weighting, propensity score adjustment, and E-value analysis to assess result robustness. Causal mediation analysis was performed to evaluate the mediating role of body temperature.ResultsAmong 1,983 eligible patients, 1,355 received acetaminophen and 628 did not. After propensity score matching (599 pairs), acetaminophen use was associated with a 31% reduction in 30-day mortality risk (HR 0.69, 95% CI: 0.56–0.85, P = 0.001). This protective effect was more pronounced in patients requiring mechanical ventilation (HR 0.53, 95% CI: 0.34–0.82) and vasopressor support (HR 0.52, 95% CI: 0.32–0.83). Enhanced benefits were also observed in younger patients (<65 years, HR 0.52, 95% CI: 0.31–0.85). Multiple sensitivity analyses yielded consistent results, with E-values ranging from 2.03 to 2.26, suggesting robust resistance to unmeasured confounding. Causal mediation analysis revealed that 54.2% (95% CI: 25.6%–187.5%, P = 0.014) of acetaminophen’s apparent protective effect was mediated through body temperature regulation during hospitalization.Conclusionacetaminophen use was associated with reduced 30-day mortality in critically ill patients with PE, with temperature control appearing to play a potential mediating role. These preliminary findings provide hypothesis-generating evidence that warrants validation in prospective randomized controlled trials before clinical implementation.